Gene network analysis of fat composition in beef of Bos taurus indicus influenced cattle - Rodriguez, Eduardo Emilio; Leal-Gutierrez, Joel D.; Carr, Chad; Mateescu, Raluca G. (Frontiers in Animal Science, 2025)
Fatty acid composition is a key determinant of beef quality, influencing traits such as flavor, tenderness, and nutritional value. Understanding the genetic regulation of fatty acid composition in beef cattle may inform strategies to improve these attributes through selective breeding. The objective of this study was to explore genomic regions associated with fatty acid composition. Genome-wide association analysis revealed several candidate genes, including HELB, PLAG1, FASN, and LZTS2, which are involved in cell growth and division and may influence lipid accumulation in adipose tissue. Gene network analysis corroborated genome-wide association study (GWAS) findings and further identified additional genes with small effects that were not detected by single-trait GWAS. This approach revealed numerous genes involved in fatty acid uptake and intracellular lipid transport, providing deeper insight into the complex genetic architecture underlying beef fatty acid composition.